Isolation of pyruvic acid producing Halomomas sp. bacterial strain from mangrove forest of Khanh Hoa province - Hoai Thu, Ngo Thi; Lan Anh, Hoang Thi; Minh Hien, Hoang Thi; Tam, Luu Thi; Thom, Le Thi; Ha, Nguyen Cam; Kawata, Yoshikazu; Hong, Dang Diem (Vietnam Journal of Biotechnology, 2018)
Pyruvic acid (pyruvate) is a central intermediate in carbon and energy metabolism in all organisms. It is widely used in the industrial biosynthesis of high - value compounds and food additives. Biotechnological pyruvate production has attracted attention as a potential alternative method of pyruvate synthesis. From 27 soil and mud samples collected from mangrove forests of Cam Ranh, Khanh Hoa province, we isolated 10 bacterial strains belonging to Halomonas genus. Among them, 9 strains were able to synthesis and secreted pyruvate in the culture medium. The maximal pyruvate production was in MC8 strain with value of 0.110 ± 0.015 g/L. MC8 strain was Gram-negative, short rod-shaped, 1,56 ± 0,07 in width, 5,09 ± 0,38 µm in length, non-flagella and nonmotile. MC8 strain was positive for oxidase and catalase activities and reduction of nitrate to nitrite and nitrogen. Cells were able to growth at salt concentrations of from 0.5 to 20%, temperature ranging from 20 to 45ºC and pH ranging from 5 to 12. The major fatty acids of MC8 biomass were C16:0; C18:1w7c và C12:0 3OH. Phylogenetic analyses based on 16S rRNA gene sequencing showed that MC8 strain possessed the highest similarity of 98.5% to the strain Halomonas flava. Based on morphological, biochemical characteristics and 16S rRNA gene sequencing, MC8 strain was identified as H. flava. This is the first study of Halophilic bacteria which is capable of pyruvate synthesis in Vietnam. Thus, these obtained results provided important insights into the production of pyruvate using Halomonas strains.